Dynamics analysis and control of a pendulum driven by a DC motor via a slider-crank mechanism - Kudra, Grzegorz; Balthazar, Jose M. [UNESP]; Tusset, Angelo M.; Wasilewski, Grzegorz; Stańczyk, Bartosz; Awrejcewicz, Jan (Elsevier, 2022)
In the present work, we deal with a dynamical analysis and passive control of chaos with magnetic rheological (MR) rotational damper in a pendulum driven by a DC motor via slider mechanism. A mathematical model for electromechanical system composed of a pendulum driven horizontally by through a DC motor and a slider-crank mechanism is presented and the parameters are estimated based on experimental data. Numerical and experimental results demonstrate that for certain values of the motor input voltage they can lead the system to chaotic behavior. For dynamic analysis, bifurcation diagrams, Poincaré sections, phase diagrams and 0–1 test are considered. In order to suppress the chaotic behavior, it is proposed to include MR rotational damper, as a passive control. In the case of the passive rotational MR damper, the influence of the introduction of the MR damper in a pendulum is performed considering the bifurcation diagrams. The numerical results show that the introduction of a passive rotational MR damper suppresses the chaotic behavior of the system. Additionally it is shown that it is possible to keep the pendulum oscillating with periodic behavior using the rotational MR damper with energizing discontinuity.
Keywords: 0–1 Test; Chaos; Dahl Model; Electromechanical System; Rotational Magnetorheological Damper; Slider mechanism